2005
DOI: 10.1086/432151
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Temperature Correlates with Evaporative Water Loss in Hylid Frogs from Northern Australia

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. ABSTRACTWe measured temperature preferences of 12 species of hylid frogs (Litoria and Cyclorana) from northern Australia in a laboratory thermal gradient. These species repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Arboreal hylid species, such as L. gracilenta , L. splendida or L. infrafrenata , might avoid excessive water loss by high cutaneous resistance, coupled with postural changes that protect their ventral surfaces (Tyler, ). This is supported by previous studies, as most of the frogs that display elevated values are arboreal frogs (Tracy & Christian, ), mainly in the families Hylidae, Rhacophoridae and Hyperoliidae. Certain clades or species within these lineages usually differ widely in cutaneous resistance to water loss (Young et al ., ; Tracy et al ., ).…”
Section: Discussionsupporting
confidence: 86%
“…Arboreal hylid species, such as L. gracilenta , L. splendida or L. infrafrenata , might avoid excessive water loss by high cutaneous resistance, coupled with postural changes that protect their ventral surfaces (Tyler, ). This is supported by previous studies, as most of the frogs that display elevated values are arboreal frogs (Tracy & Christian, ), mainly in the families Hylidae, Rhacophoridae and Hyperoliidae. Certain clades or species within these lineages usually differ widely in cutaneous resistance to water loss (Young et al ., ; Tracy et al ., ).…”
Section: Discussionsupporting
confidence: 86%
“…through thermoregulation. In fact, several species select lower temperatures when dehydrated (Shoemaker et al 1989;Tracy et al 1993;Williams and Wygoda 1993) or in dry conditions (Malvin and Wood 1991), and species that are more prone to dehydration tend to select lower temperatures than less vulnerable ones (Tracy and Christian 2005). However, lower temperatures would probably not benefit R. granulosa, as dehydration effects on hopping speed were independent of body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of T p selection in lizards is widely accepted, some authors have suggested the existence of a tradeoff between T p and evaporative water loss (WL ;Bruce 1990;Bowker 1993); those species capable of reducing WL while remaining mobile have the best chances of having a precise temperature control (Tracy 1976;Buttemer 1990) without experiencing the cooling and dehydrating effects of evaporation (Tracy and Christian 2005). Studies assessing water loss rates (WLRs) have demonstrated that lizards can also modify their dehydration levels as an adaptation to novel environments (e.g., Kolbe et al 2014), but they also report cases of strong phylogenetic influences on this trait (e.g., Mautz 1982;García-Muñoz and Carretero 2013;Osojnik et al 2013;Carneiro et al 2015).…”
Section: Introductionmentioning
confidence: 99%